Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae) - Guan, Wei; Li, Houhun (Zootaxa, 2016)
The genus Thylacosceles Meyrick, 1889 is recorded from China for the first time. Thylacosceles nephroides sp. nov., T. clavata sp. nov., T. cuneiformis sp. nov. and T. ellipsoidala sp. nov. are described as new. Photographs of adults and genital illustrations are provided, along with a key to the genus in China.